DEVELOPING LEARNING INDEPENDENCE THROUGH UTILIZATION OPEN DIGITAL LEARNING RESOURCES: A LITERATURE REVIEW - Elfina Indah Dwi Meila; Ikrima Nur Hafizhah; Apriliantoni (STMIK Indonesia Banda Aceh, 2026)
The development of digital technology has brought about significant changes in education, particularly in students' independent learning processes. The use of open digital learning resources is an alternative that can support increased independent learning because it provides broad, flexible, and easily accessible access to information. This study aims to describe how open digital learning resources can foster independent learning in students. The method used is a literature review, reviewing various journals, books, and scientific articles related to digital learning and independent learning. The results of the study indicate that the use of open digital learning resources can increase students' learning motivation, time management skills, learning responsibility, and critical thinking skills. Furthermore, the use of digital platforms also provides opportunities for students to learn according to their own needs and pace. Thus, open digital learning resources can be an effective tool in building a culture of independent learning in the digital era.